Dissociation of impulsivity and aggression in mice deficient for the ADHD risk gene Adgrl3: Evidence for dopamine transporter dysregulation. (15th September 2019) - Mortimer, Niall; Ganster, Tatjana; O'Leary, Aet; Popp, Sandy; Freudenberg, Florian; Reif, Andreas; Soler Artigas, María; Ribasés, Marta; Ramos-Quiroga, Josep Antoni; Lesch, Klaus-Peter; Rivero, Olga
Abstract: Adhesion G protein-coupled receptor L3 (ADGRL3, LPHN3) has putative roles in neuronal migration and synapse function. Various polymorphisms in ADGRL3 have been linked with an increased risk of attention deficit/hyperactivity disorder (ADHD). In this study, we examined the characteristics of Adgrl3 -deficient mice in multiple behavioural domains related to ADHD: locomotive activity, impulsivity, gait, visuospatial and recognition memory, sociability, anxiety-like behaviour and aggression. Additionally, we investigated the effect of Adgrl3 -depletion at the transcriptomic level by RNA-sequencing three ADHD-relevant brain regions: prefrontal cortex (PFC), hippocampus and striatum. Adgrl3 −/− mice show increased locomotive activity across all tests and subtle gait abnormalities. These mice also show impairments across spatial memory and learning domains, alongside increased levels of impulsivity and sociability with decreased aggression. However, these alterations were absent in Adgrl3 +/ − mice. Across all brain regions tested, the numbers of genes found to exhibit differential expression was relatively small, indicating a specific pathway of action, rather than a broad neurobiological perturbation. Gene-set analysis of differential expression in the PFC detected a number of ADHD-relevant pathways including dopaminergic synapses as well as cocaine and amphetamine addiction. The Slc6a3 gene coding for the dopamine transporter was the most dysregulated gene in the PFC. Unexpectedly, several neurohormone/peptides which are typically only expressed in the hypothamalus were found to be dysregulated in the striatum. Our study further validates Adgrl3 constitutive knockout mice as an experimental model of ADHD while providing neuroanatomical targets for future studies involving ADGRL3 modified models. This article is part of the Special Issue entitled 'Current status of the neurobiology of aggression and impulsivity'. Highlights: ADGRL3 knockout as a model of ADHD. Increased activity and reduced aggression in ADGRL3 knockout mice. Loss of ADGRL3 impairs learning and memory in mice. Region-specific transcriptomic analysis of controls and ADGRL3 knockout mice. Strong downregulation of dopamine transporter in the prefrontal cortex of ADGRL3 knockout mice.